2012
DOI: 10.1111/jre.12033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of Zingiber cassumunar extracts on lipopolysaccharide‐induced cyclooxygenase‐2 and matrix metalloproteinase expression in human gingival fibroblasts

Abstract: Our results indicate that Z. cassumunar extracts inhibit COX-2 and MMP-2 production by LPS-activated human gingival fibroblasts through blocking the proinflammatory signaling pathway involving ERK1/2, JNK and p38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
(62 reference statements)
0
13
0
3
Order By: Relevance
“…34 Although the underlying mechanism of the action of Phlai and compound D on PMAmediated MMP-9 activation in airway epithelial cells is not clear at present, our previous work has shown that crude Phlai extract suppresses MMP-2 via the inhibition of ERK activation in LPSstimulated human gingival fibroblasts. 35 Therefore, it is conceivable that Phlai and compound D may suppress PMA-induced MMP-9 production in NCI-H292 cells through the inhibition of PAR-2 and ERK activation. In conclusion, our results show that crude phlai extract and its constituent compound D inhibit the cleavage of pro-MMP-9 and MMP-9 production in PMA-induced airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although the underlying mechanism of the action of Phlai and compound D on PMAmediated MMP-9 activation in airway epithelial cells is not clear at present, our previous work has shown that crude Phlai extract suppresses MMP-2 via the inhibition of ERK activation in LPSstimulated human gingival fibroblasts. 35 Therefore, it is conceivable that Phlai and compound D may suppress PMA-induced MMP-9 production in NCI-H292 cells through the inhibition of PAR-2 and ERK activation. In conclusion, our results show that crude phlai extract and its constituent compound D inhibit the cleavage of pro-MMP-9 and MMP-9 production in PMA-induced airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Terpinen-4-ol merupakan salah satu golongan terpenoid yang merupakan konstituen utama yang terkandung di dalam rimpang bangle (Zingiber cassumunar) dengan kandungan mencapai 30-35% dari keseluruhan senyawa yang terkandung di dalam rimpang bangle (Bhuiyan, 2018). Hasil uji in vitro menunjukkan bahwa ekstrak etanol Zingiber cassumunar dapat menghambat COX dan produksi matriks metalloproteinase MMP-2 dengan memblokir jalur sinyal proinflamasi yang melibatkan ERK 1/2, JNK, dan p38 pada jalur MAPK (Koontongkaew et al, 2013).…”
Section: Pendahuluanunclassified
“…,5΄΄΄-trimethoxy-sty ryl]cyclohex-1-ene (compound C) and DMPBD reduced PGE 2 and COX-2 expression in dental pulp inflammation Koontongkaew et al, 2013). In addition, curcumin, which was found as a minor compound in Z. cassumunar, has an ability to suppress the expression of COX-2 (Surh and Kundu, 2007).…”
Section: Chemical Constituents and Anti-inflammatory Activity Of Prasmentioning
confidence: 99%